2021
DOI: 10.17159/2310-3833/2021/vol51n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perceptual Deficits in Different Types of Cerebral Palsy

Abstract: BSc. OT (Wits) MSc. OT (Wits).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 81 publications
1
6
3
Order By: Relevance
“…A previous study, including children with unilateral CP aged between 5 years and 18 years, reported that visual-perceptual functions (measured according to the TVPS-3) did not differ between those with different levels of manual ability (measured according to the MACS). 6 On the contrary, we found a significant difference in visual-perceptual functions (visual figure-ground subtest of the TVPS-4 and the visual perception subtest of the Beery-VMI) between children in MACS levels I and III. The study by Berelowitz and Franzsen 6 included different subtypes of CP, a different age range, and a different version of the TVPS, which might account for the differences from our results.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…A previous study, including children with unilateral CP aged between 5 years and 18 years, reported that visual-perceptual functions (measured according to the TVPS-3) did not differ between those with different levels of manual ability (measured according to the MACS). 6 On the contrary, we found a significant difference in visual-perceptual functions (visual figure-ground subtest of the TVPS-4 and the visual perception subtest of the Beery-VMI) between children in MACS levels I and III. The study by Berelowitz and Franzsen 6 included different subtypes of CP, a different age range, and a different version of the TVPS, which might account for the differences from our results.…”
Section: Discussioncontrasting
confidence: 70%
“…This is in contrast with previous studies reporting that children with left-sided unilateral CP showed lower performance compared with right-sided unilateral CP or NTD. 6,7 This was explained by the fact that the right hemisphere of the brain processes visuospatial function. Differences with our findings could be explained by more widespread (bilateral) lesions in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations